Model Safety Behaviour untuk Mengurangi Accident dalam Menjaga Keberlanjutan Industri Pariwisata Madura - Faidal, Faidal (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
The tourism industry is a key player in the global economy, generating billions of dollars in revenue and providing jobs for millions of people around the world, contributing more than 6 trillion annually, employing more than 250 million people, and generating 7% of global GDP (World Travel Tourism Council, 2018). However, as the industry grows, comes the responsibility to ensure the safety and well-being of employees and tourist visitors. Safety is critical in maintaining the reputation and sustainability of the tourism industry, while employee safety is critical in ensuring a productive and positive work environment. In recent years, there has been growing concern about safety practices in the tourism industry, prompting researchers to investigate the factors that contribute to safe behavior among employees. This research focuses on the impact of safety knowledge and safety behavior in the tourism industry so that it has an impact on reducing the number of accidents. The aim of this research is to provide insights that can help improve safety practices and ensure a positive and safe experience for employees and tourists at destinations in Madura and reduce accident incidents.